2003
DOI: 10.1080/j006v23n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses to Tactile Stimuli in Children with Cerebral Palsy

Abstract: Children with cerebral palsy often have difficulty processing tactile information. Assessment of tactile processing in children with cerebral palsy frequently relies on the use of informal clinical observations, checklists, and sensory histories without established psychometric properties. It is proposed that a formal approach to the assessment of behavioral responses to tactile stimuli will provide a better understanding of the tactile processing of children with cerebral palsy. This approach also has potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 47 publications
(30 reference statements)
0
15
0
3
Order By: Relevance
“…There are ubiquitous reports of impaired discriminative tactile abilities in CP (see Clayton et al (2003) for a comprehensive review), and these impairments are closely associated with motor difficulties (van Heest et al 1993). Wingert et al (2008) found texture perception to be impaired in a CP sample relative to controls.…”
Section: Psychophysical Measures Somatosensory Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are ubiquitous reports of impaired discriminative tactile abilities in CP (see Clayton et al (2003) for a comprehensive review), and these impairments are closely associated with motor difficulties (van Heest et al 1993). Wingert et al (2008) found texture perception to be impaired in a CP sample relative to controls.…”
Section: Psychophysical Measures Somatosensory Processingmentioning
confidence: 99%
“…There is also some overlap between symptoms of ASD and Fragile X. Cerebral palsy (CP) is a group of non-progressive disorders primarily affecting motor development that arises from insult or injury in the prenatal or perinatal environment. The motor deficits seen in CP are primarily abnormalities in muscle tone, and are associated with widespread differences in somatosensory perception as well (Clayton et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…Even if the protective mechanism is not fully understood at the moment, enriched environment can be a promising strategy in treating asphyctic newborns also in human clinical therapy. Similarly, the neuroprotective effects of tactile stimuli were first described in rats, and are now used in neonatal care, as part of standard handling [80]. …”
Section: Resultsmentioning
confidence: 99%
“…In this sense, studies with transcranial magnetic stimulation (TMS) have provided evidence of ipsilateral corticospinal projections from the undamaged motor cortex to the affected hand [15,19-24]. Moreover, it has been proposed that somatosensory deficits could be due to secondary effects provoked by motor limitation [25]. Thus, reduced and stereotypical pattern of spontaneous movements in patients with hemiplegic CP would result in abnormal sensory feedback and altered cortical reorganization, thus leading to asymmetric somatosensory processing deficits [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been proposed that somatosensory deficits could be due to secondary effects provoked by motor limitation [25]. Thus, reduced and stereotypical pattern of spontaneous movements in patients with hemiplegic CP would result in abnormal sensory feedback and altered cortical reorganization, thus leading to asymmetric somatosensory processing deficits [25,26]. A case study by Ragazzoni and colleagues (2002) [27] has further showed that somatosensory function of the affected (right) arm was preserved, whereas motor function was poor despite fast-conducting ipsilateral cortico-motoneuronal output from primary motor cortex of the intact hemisphere to the affected arm.…”
Section: Introductionmentioning
confidence: 99%